PSYCHOLOGICAL-PEDAGOGICAL OPPORTUNITIES OF NATIONAL CRAFTS OF SCHOOL PUPILS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The psychological and pedagogical potential of schoolchildren for national crafts is logically and scientifically stated. In today's era of globalization, modern psychology and pedagogy are becoming more widespread in all disciplines taught in the system of continuing education. This is directly related to the national craft taught in secondary schools, which allows students to think creatively in the educational process, to apply what they have learned in practice.